Physical Properties of Emulsion-Based Hydroxypropyl Methylcellulose Films: Effect of Their Microstructure - Osorio-Lira, F (2012)
The initial characteristics of emulsions and the rearrangement of the oil droplets in the film matrix during film drying, which defines its microstructure, has an important role in the physical properties of the emulsion-based films. The objective of this work was to study the effect of the microstructure (two droplet size distributions) and stability (with or without surfactant) of HPMC oil-in-water emulsions over physical properties of HPMC emulsion-based edible films. HPMC was used to prepare sunflower oil-in-water emulsions containing 0.3 or 1.0% (w/w) of oil with or without SDS, as surfactant, using an ultrasonic homogenizer. Microstructure, rheological properties and stability of emulsions (creaming) were measured. In addition, microstructure, coalescence of oil droplets, surface free energy, optical and mechanical properties and water vapor transfer of HPMC films were evaluated. Image analysis did not show differences among droplet size distributions of emulsions prepared at different oil contents; however, by using SDS the droplet size distributions were shifted to lower values. Volume mean diameters were 3.79 and 3.77 ?m for emulsions containing 0.3 and 1.0% without surfactant, respectively, and 2.72 and 2.71 ?m for emulsions with SDS. Emulsions formulated with 1.0% of oil presented higher stability, with almost no change during 5 and 3 days of storage, for emulsions with and without SDS, respectively. Internal and surface microstructure of emulsion-based films was influenced by the degree of coalescence and creaming of the oil droplets. No effect of microstructure over the surface free energy of films was found. The incorporation of oil impaired the optical properties of films due to light scattering of light. Addition of oil and SDS decreased the stress at break of the emulsion-based films. The replace of HPMC by oil and SDS produce a lower "amount" of network structure in the films, leading to a weakening of their structure. The oil content and SDS addition had an effect over the microstructure and physical properties of HPMC-based emulsions which lead to different microstructures during film formation. The way that oil droplets were structured into the film had an enormous influence over the physical properties of HPMC films. © 2012 Elsevier Ltd. All rights reserved.